Relationship of the External Environment to the Dynamics of Organizational Culture a Study of Organizational Anthropology - Safriadi Safriadi (Budapest International Research and Critics University, 2022)
This study aims to determine organizational external factors that affect organizational existence and anticipatory strategies at the financing company PT. Fleet Finance in Makassar. The research method in this study is a qualitative descriptive method. Research informants are managers, employees and customers of companies that are determined purposefully. The results showed that the form of resistance to the external environment in the form of fixed rules as a consideration for the company, but with a strategy that still maximizes the profile by minimizing risk. Environmental threats from similar companies are anticipated with the advantages of relationships with the network of companies that are in the same group within the Kalla Group, more competitive discounts with other companies and massive promotions both on social media and at auto shows. The global economic slowdown is anticipated with the following strategies: (1) The Company implements a communication strategy that emphasizes product and service excellence, not only promoting the issue of halal and haram products, (2) Opening new financing products that can take the form of take over from other funding (3) Increasing the vehicle business segment, such as pick up cars and trucks, and (4) Evaluating the company's financing activities by trying to normalize all vehicle financing investments.